The Effect of Education Performance on Poverty in Indonesia - Putri Hogi; Muhammad Amir Arham; Boby Rantow Payu (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study uses a quantitative approach with a panel data regression analysis method. The data used are secondary data from 38 provinces in Indonesia during the 2015–2024 period (380 observations), which are sourced from the Central Statistics Agency (BPS). The selection of the best model is carried out through the Chow Test, Hausman Test, and Lagrange Multiplier Test, which results in the Random Effect Model (REM) as the most appropriate model to use. Based on the results of the study, it shows that simultaneously, all variables of educational performance have a significant effect on poverty in Indonesia with an adjusted R² value of 88.58%. Partially, the Literacy Rate (AMH) has a negative and significant effect on poverty, where every 1% increase in AMH will reduce the poverty rate by 3.37% School Participation Rate (APS) also has a negative and significant effect, where every 1% increase in APS will reduce poverty by 0.28%. Meanwhile, the Average School Length (RLS) shows a negative but not significant effect on poverty, indicating that the quantity of education alone is not enough without being balanced with improving the quality and relevance of education to the needs of the labor market.